A Facile and Efficient Modification of CNTs for Improved Fischer–Tropsch Performance on Iron Catalyst: Alkali Modification. Issue 8 (18th March 2016) - Liu, Renjie; Xu, Yan; Li, Zhenhua; Ma, Xinbin
Abstract: The front cover artwork for Issue 08/2016 is provided by Prof. Dr. Zhenhua Li, Prof. Dr. Xinbin Ma, and co‐workers from Tianjin University (P.R. China). The image shows that an iron catalyst supported on alkali‐modified carbon nanotubes (CNTs) exhibits extraordinary Fischer–Tropsch catalytic performance and efficient application to diesel production. See the Communication itself at http://dx.doi.org/10.1002/cctc.201501219 . Abstract : "It is exciting that the Fe/CNTs catalyst achieved enhanced activity and stability" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttp://dx.doi.org/10.1002/cctc.201501219 .